2011
DOI: 10.1002/mds.24025
|View full text |Cite
|
Sign up to set email alerts
|

Emotional processing in Parkinson's disease: A systematic review

Abstract: Parkinson's disease provides a useful model for studying the neural substrates of emotional processing. The striato-thalamo-cortical circuits, like the mesolimbic dopamine system that modulates their function, are thought to be involved in emotional processing. As Parkinson's disease is histopathologically characterized by the selective, progressive, and chronic degeneration of the nigrostriatal and mesocorticolimbic dopamine systems, it can therefore serve as a model for assessing the functional role of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
149
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 105 publications
(101 reference statements)
10
149
0
1
Order By: Relevance
“…In works related to emotion recognition using physiological signal, acquiring emotional data that corresponds to specific emotional state is challenging, because of the subjective nature of the emotions and cognitive dependence of physiological signals which requires the emotional states to be elicited internally in the participant. Until now, most studies on emotion recognition in PD have used only facial stimuli, prosodic stimuli, or music stimuli (Gray and Tickle-Degnen, 2010;Lima et al, 2013;Péron et al, 2012). In addition, a number of emotion induction techniques Emotional state classification in PD 10 using pictures, sounds, music, or multimodal approach (combination of audio and visual) have been used to elicit the target emotions in healthy controls (Baumgartner et al, 2006;Lin et al, 2010;Murugappan et al, 2010;Petrantonakis and Hadjileontiadis, 2011;Wang et al, 2013).…”
Section: Stimulus Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In works related to emotion recognition using physiological signal, acquiring emotional data that corresponds to specific emotional state is challenging, because of the subjective nature of the emotions and cognitive dependence of physiological signals which requires the emotional states to be elicited internally in the participant. Until now, most studies on emotion recognition in PD have used only facial stimuli, prosodic stimuli, or music stimuli (Gray and Tickle-Degnen, 2010;Lima et al, 2013;Péron et al, 2012). In addition, a number of emotion induction techniques Emotional state classification in PD 10 using pictures, sounds, music, or multimodal approach (combination of audio and visual) have been used to elicit the target emotions in healthy controls (Baumgartner et al, 2006;Lin et al, 2010;Murugappan et al, 2010;Petrantonakis and Hadjileontiadis, 2011;Wang et al, 2013).…”
Section: Stimulus Materialsmentioning
confidence: 99%
“…Over the last decade, there has been an increasing attention to the role played by emotional processes in PD (Gray and Tickle-Degnen, 2010;Péron et al, 2012). Evidence indicates the individuals with PD have deficits in recognizing emotions from prosody (Dara et al, 2008;Pell and Leonard, 2003;Yip et al, 2003) and facial expressions (Ariatti et al, 2008;Clark et al, 2008;Dujardin et al, 2004), although not all findings have been consistent.…”
Section: Introductionmentioning
confidence: 99%
“…These lead to difficulties in describing bodily sensations, physiological arousal and feelings, expressing emotions, and identifying others' emotions from prosody and facial expression 8, 9, 10. Facial emotion recognition (FER) is one of the most basic aspects of emotional functioning and one of the most critical components of social behaviors.…”
mentioning
confidence: 99%
“…However, studies assessing FER in PD still report contradictory results. Although 2 reviews and 1 meta‐analysis revealed an FER deficit in PD and outlined potential biasing factors,9, 11, 12 the origins of this inconsistency are unclear, and several questions remain unanswered. For instance, what is the actual effect of dopaminergic medication on FER in PD?…”
mentioning
confidence: 99%
“…Non-motor symptoms, including disruptions in processing of emotional information [4,5] have been found in over 50% of newly diagnosed PD patients [6] and can appear in any stage of disease progression [7]. Interestingly, social cognitive dysfunction has been found before the appearance of motor disturbances in PD [8].…”
Section: Introductionmentioning
confidence: 99%